BOCADE: Improving the User Experience (UX) of Competitive Programming Contestants with a Visual Studio Code Extension - Santos, Luiz Gustavo Albuquerque dos; Ribeiro, Fabíola G. C.; Oliveira, Kenia S. de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.241858, 2024)
The BOCA programming contest management system provides a web interface for contestants. Moreover, contestants use standard code editors to develop their code. However, these editors are not optimized for the specific context of use of competitive programming. Therefore, in this paper, we present BOCADE, an extension for Visual Studio Code with the following functionalities: built-in BOCA interface and PDF viewer, automated test cases extraction and execution panel, and a mechanism for quick workspace organization. To evaluate the extension, two usability tests were conducted — a formative and a summative. The results suggests that the extension provides a superior UX for competitive programming contestants compared to the traditional setup.